The Trophic state of Patagonian Argentinean lakes and its relationship with depth distribution in sediment Phosphorus - Temporetti, Pedro Felix (2014)
The parameters used to determine the trophic state of a water body are: total phosphorus (TP), transparency (Secchi disk depth) and chlorophyll a. However, these parameters show strong seasonal fluctuations which may hinder the estimation of trophic state. Some authors have proposed that sediments be used as an additional tool to evaluate the trophic state of a water body. The aim of this study was to determine the depth distribution of sediment TP in relation with the lake trophic state. Nine sediment corers from water bodies located in Patagonian Region (Argentina) were studied. The nutrient concentrations in pore water and in sediments were analyzed. The results obtained showed that there is a relationship between the depth distribution of sediment TP and the trophic state for all studied environments. Two exceptions were noted to this general pattern (Lakes Caviahue and Lácar). Our findings indicate that both pore water and sediments could be considered as the best parameters to estimate the tropic state of a water body compared to the water column.